Surgical Outcome and Oncological Survival of Osteofibrous Dysplasia-Like and Classic Adamantinomas: An International Multicenter Study of 318 Cases. (7th October 2020) - Schutgens, E.M.; Picci, P.; Baumhoer, D.; Pollock, R.; Bovée, J.V.M.G.; Hogendoorn, P.C.W.; Dijkstra, P.D.S.; Rueten-Budde, A.J.; Jutte, P.C.; Traub, F.; Leithner, A.; Tunn, P.-U.; et al.
Abstract : Background: Osteofibrous dysplasia-like adamantinoma (OFD-AD) and classic adamantinoma (AD) are rare, neoplastic diseases with only limited data supporting current treatment protocols. We believe that our retrospective multicenter cohort study is the largest analysis of patients with adamantinoma to date. The primary purpose of this study was to describe the disease characteristics and evaluate the oncological outcomes. The secondary purpose was to identify risk factors for local recurrence after surgical treatment and propose treatment guidelines. Methods: Three hundred and eighteen confirmed cases of OFD-AD and AD for which primary treatment was carried out between 1985 and 2015 were submitted by 22 tertiary bone tumor centers. Proposed clinical risk factors for local recurrence such as size, type, and margins were analyzed using univariable and multivariate Cox regression analysis. Results: Of the 318 cases, 128 were OFD-AD and 190 were AD. The mean age at diagnosis was 17 years (median, 14.5 years) for OFD-AD and 32 years (median, 28 years) for AD; 53% of the patients were female. The mean tumor size in the OFD-AD and AD groups combined was 7.8 cm, measured histologically. Sixteen percent of the patients sustained a pathological fracture prior to treatment. Local recurrence was recorded in 22% of the OFD-AD cases and 24% of the AD cases. None of the recurrences in the OFD-AD group progressed to AD. Metastatic disease was found in 18% of the AD cases and fatal disease, in 11% of the AD cases. No metastatic or fatal disease was reported in the OFD-AD group. Multivariate Cox regression analysis demonstrated that uncontaminated resection margins (hazard ratio [HR] = 0.164, 95% confidence interval [CI] = 0.092 to 0.290, p < 0.001), pathological fracture (HR = 1.968, 95% CI = 1.076 to 3.600, p = 0.028), and sex (female versus male: HR = 0.535, 95% CI = 0.300 to 0.952, p = 0.033) impacted the risk of local recurrence. Conclusions: OFD-AD and AD are parts of a disease spectrum but should be regarded as different entities. Our results support reclassification of OFD-AD into the intermediate locally aggressive category, based on the local recurrence rate of 22% and absence of metastases. In our study, metastatic disease was restricted to the AD group (an 18% rate). We advocate wide resection with uncontaminated margins including bone and involved periosteum for both OFD-AD and AD. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.